Characteristics of Multicultural Islamic Education Management: (Research at Miftahul Huda Manonjaya Tasikmalaya Islamic Boarding School and El-Bayan Cilacap Islamic Boarding School) - Udung Hari Darifah; Asep Nursobah; Sarbini Sarbini; Mohamad Jaenudin (International Journal of Islamic Educational Research, 2025)
The research departs from educational problems in Islamic boarding schools with distinctive educational characteristics and the diversity of cultural backgrounds of students. So researchers are interested in conducting a more in-depth analysis of a harmonious environment despite having students with diverse cultural backgrounds. The purpose of the study is to identify; 1) the characteristics of multicultural Islamic education planning, 2) the characteristics of organizing multicultural Islamic education, 3) Identification of the characteristics of implementing multicultural Islamic education, 4) Identification of the characteristics of supervision of multicultural Islamic education, 5) Analysis of the impact of the characteristics of multicultural Islamic education management in producing moderate students. The research framework departs from theory of multicultural education management in Islamic boarding schools which includes; planning, organizing, implementing, and supervising educational programs in Islamic boarding schools. Managing the elements of education in Islamic boarding schools in; objectives, values, curriculum, teaching methods and facilities and funds, carried out by the Kiyai Ustadz Santri Manager will have an impact on the attitude of religious moderation in students with indications of national commitment, tolerance, anti-violence, accommodating to local culture. This study used a qualitative approach, using ethnography. Data collection techniques are carried out through interviews, observations, and documentation analysis. Data analysis technique uses the Miles and Huberman analysis technique. The validity test is carried out with data validity by conducting tests; on credibility, transferability, dependability, and confirmability. Results of the study found that the characteristics of multicultural education management in Islamic boarding schools: First, Planning in the form of a curriculum containing multicultural values, involving various elements of the Islamic boarding school through deliberation and open meetings of curriculum preparation studies, integrating the madrasah curriculum with Islamic boarding school. Second, organizing; there is empowerment in fostering Islamic boarding schools, Conventional traditional systems, and Guidance patterns depending on the figure of kiai, the existence of organizational work procedures. Third, Implementation of education is carried out; structured through learning classification, planned, organized, and evaluated with the basic pattern of Islamic boarding school education, internalized in attitudes, methods, and exemplary behavior of the kiai. Fourth, Supervision of learning through assessment of learning of multicultural values, Tests are contextual and comprehensive. Fifth, impact of the characteristics of multicultural Islamic education management in producing students who are able to act in the middle by prioritizing Islamic brotherhood and basyariyah, are tolerant for the sake of realizing Islam rahmatan lil aalamiin.